Noninvasive Technique to Monitor the Pressure under a Cast: A Mobile Application-Friendly Bluetooth Pressure Sensor - Mahir Mahirogullari; Serkan Surucu; Mehmet Halis Cerci; Mahmud Aydin; Abdulkadir Kayikli; Oguzhan Gunduz (International Journal of Clinical Practice)
Aim. The purpose of this study was to design a sensor that could monitor the skin-cast contact surface pressure (SCCSP) of a limb under a cast and inform the user via a mobile application when the pressure increases. Methods. In this experimental study, an infant sphygmomanometer cuff was initially placed on the forearm of 10 volunteers. A pressure sensor with a Bluetooth chip was then placed on the volar aspect of the forearm. Short arm plaster was applied with synthetic cast material. The SCCSP under the plaster was measured by the sensor and the measured values were transmitted to a mobile application via a Bluetooth chip. The mobile application processed the data from the chip and converted it to mmHg. Results. Intracompartmental pressure (ICP) values were categorized as 0, 10, 20, 30, 40, 50, 60, and 75 mmHg. The highest SCCSP was 75 mmHg CP, while the lowest was 0 mmHg CP. The correlation coefficient of the mean pressure values was 0.993 (p≤0.001) (SD 0.002, range 0.989–0.997), and there was a significant relationship between ICP and SCCSP values (p≤0.05). Conclusion. We can monitor SCCSP, detect limb swelling, and notify the user via a mobile application by using Bluetooth pressure sensors.